Methods in special education - Kauffman, James M. ;Pullen, Paige C. (New York : McGraw Hill Education, 1967)
This book is intended to be a combination text and source book in special education.
1. Exceptionality and Special Education -- 2. Current practices for meeting the needs of exceptional learners -- 3. Multicultural and bilingual aspects of Special Education -- 4. Parents and families -- 5. Learners with intellectual and developmental disabilities -- 6. Learners with learning disabilities -- 7. Learners with attention deficit hyperactivity disorder -- 8. Learners with emotional and behavioral disorders -- 9. Learners with autism spectrum disorders -- 10. Learners with communication disorders -- 11. Learners who are deaf or hard of hearing -- 12. Learners with blindness or low vision -- 13. Learners with low-incidence, multiple, and severe disabilities -- 14. Learners with physical disabilities and other health impairments -- 15. Learners with special gifts and talents.
Includes bibliographical references and index.
Keywords: SPECIAL EDUCATION